2014
DOI: 10.1109/tgrs.2013.2253109
|View full text |Cite
|
Sign up to set email alerts
|

Improvements on Lightning Density Estimation Based on Analysis of Lightning Location System Performance Parameters: Brazilian Case

Abstract: Abstract-Density maps are one of the most common and powerful lightning data applications, and they are more efficient the more detailed they are. When working with CG lightning data from lightning location systems, some aspects must be included in the analysis to overcome network performance variations. Two parameters are typically used to evaluate system performance: detection efficiency (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Schulz et al 2005;Feudale et al 2013;Poelman et al 2016). Bourscheidt et al (2014); Kingfield et al (2017); Simon et al (2017) demonstrated how the cell-count method is unsuitable for smaller cell sizes corroborating the theoretical considerations in Diendorfer (2008), who used the Poisson distribution to derive the minimum number of flashes in a cell required for reaching a specified accuracy. The Poisson distribution is the limiting case of the binomial distribution, which describes the binary event of the occurrence of lightning (yes/no).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Schulz et al 2005;Feudale et al 2013;Poelman et al 2016). Bourscheidt et al (2014); Kingfield et al (2017); Simon et al (2017) demonstrated how the cell-count method is unsuitable for smaller cell sizes corroborating the theoretical considerations in Diendorfer (2008), who used the Poisson distribution to derive the minimum number of flashes in a cell required for reaching a specified accuracy. The Poisson distribution is the limiting case of the binomial distribution, which describes the binary event of the occurrence of lightning (yes/no).…”
Section: Discussionsupporting
confidence: 65%
“…2a, on the other hand, produced with the generalized additive model (GAM) method, is devoid of noise and yet provides intricate spatial details for any given day in the lightning season (of which the map shows five). Similarly spatially detailed climatological maps can be achieved using a bivariate Gaussian error distribution for each lightning discharge instead of a precise location (Bourscheidt et al 2014;Kingfield et al 2017). The advantage of the GAM method is its ability to harness regional, elevational and seasonal characteristics that cells share that need not be immediately "next" to another and thus make a high combined spatio-temporal resolution possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen years of data were considered, corresponding to the austral summer period from 1999 to 2014, of which the 1999–2010 data are from the RINDAT network and the data from 2011–2014 are from the BrasilDAT network. For the study period, RINDAT showed detection efficiency above 80% and BrazilDAT above 90% (Naccarato and Pinto, ; Bourscheidt et al ., ). These values indicate that both networks had full conditions to use their data.…”
Section: Methodsmentioning
confidence: 97%
“…1 km) grid or derived directly from the LLS data using a kernel density estimator. Usually, when the location error of each CG lightning strike observed by LLS is given, the probabilistic computational methods based on confidence ellipse are recommendable for deriving CG strike densities in high spatial resolution (Bourscheidt et al 2014;Etherington and Perry 2017). However, the ADTD doesn't provide the location error of single CG lightning strike.…”
Section: Cg Strike Density Correctionmentioning
confidence: 99%